Risk-based Supervision of Pension Funds : Emerging Practices and Challenges - Brunner, Greg; Hinz, Richard; Rocha, Roberto (Washington, DC : World Bank, 2012)
Risk-based supervision of pension funds grew out of a project that was jointly conducted by the World Bank and the International Organization of Pension Supervisors (IOPS). The project was initiated in response to the increasing interest in the development of innovative approaches to pension supervision from the member countries of both institutions. The volume provides an initial assessment of the development of risk-based supervision of pension funds in four countries that have been pioneering the development of risk-based supervision methods in various forms. The volume is comprised of a summary chapter and in-depth studies of the experience in four individual countries-Australia, Denmark, Mexico, and Netherlands. These four country studies were prepared by experts familiar with the systems in each of the countries. The studies have been edited by World Bank staff to ensure a consistent approach to the analysis of the various countries' systems. Models of risk-based supervision demonstrate the benefits of moving away from an approach based on strict compliance, specific rules, and quantitative controls toward an approach that puts more emphasis on the identification and management of relevant risks. A risk-based approach encourages supervised entities to place a greater focus on risk management in their daily operations, which promotes a stronger pension system and more effective outcomes for the members of the system. It is also expected that moving to a risk-based approach to supervision will enhance the ability of supervisors to focus resources on areas of highest risk, which will, over time, result in a more efficient use of supervisory resources.